New species and new distributional records of the hygropetric water scavenger beetle genus Oocyclus Sharp (Coleoptera, Hydrophilidae) from the Brazilian Shield - Alencar, Janderson Batista R.; Short, Andrew Edward Z.; Hamada, Neusa (Zootaxa, 2022)
Nine new species of the water scavenger beetle genus Oocyclus Sharp, 1882 are described from the Brazilian Shield: O. ecolab sp. n., O. espinhacu sp. n., O. giganteus sp. n., O. humboldti sp. n., O. lacia sp. n., O. ovalis sp. n., O. sulcatus sp. n., O. thrixdiastematus sp. n., and O. thysanus sp. n. New locality records are provided for four species previously known from Brazil: O. rotundus Clarkson & Short, 2012, O. pilosus Jordão, Clarkon & Ferreira-Jr, 2018, O. xanthus Clarkson & Short, 2012 and O. yubai Clarkson & Short, 2012. All species are associated with rock-face seepages such as wet rocks, waterfalls, and seepages. An updated key to the Brazilian species of Oocyclus is provided.